Aplikasi NodeMCU ESP8266 Untuk Monitoring Kelembaban Tanah Berbasis Internet of Things - Rivan Sarwansah; Usman Jaelani; Andi Hasad; Setyo Supratno; Sugeng (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
Each school will determine the role model at the end of each semester to measure the competency test of each student. However, in determining exemplary students in schools, it always creates inspiration among the teacher councils because each teacher council has each to see exemplary students in schools. The Support System (SPK) or Decision Support System (DSS) is an information system intended to assist schools in solving student decision problems. One of the methods used in the decision support system is the Weighted product. The criteria used are academic and non-academic. Furthermore, the criteria will be divided into sub-criteria according to the provisions of the school. With this model student application, it really helps the teacher council to solve the problems that students expect at school. Keywords: Decision Support System, Exemplary Student, School, Weighted Product Abstrak Setiap sekolah akan menentukan siswa teladan setiap akhir semester untuk mengukur uji kompetensi setiap siswa. Namun dalam menentukan siswa teladan di sekolah selalu menimbulkan perdebatan antar dewan guru karena setiap dewan guru mempunyai pilihan masing masing untuk di jadikan siswa teladan dalam sekolah. Sistem Pendukung Keputusan (SPK) atau Decision Support System (DSS) merupakan suatu sistem informasi yang ditujukan untuk membantu sekolah dalam memecahkan masalah penentuan siswa teladan. Salah satu metode yang digunakan dalam sistem pendukung keputusan adalah Weighted product. Kriteria yang dipergunakan yaitu akademik dan non akademik. Selanjutnya dari kriteria tersebut akan dibagi menjadi subkriteria sesuai ketentuan dari sekolah. Dengan adanya aplikasi penentuan siswa teladan ini sangat membantu dewan guru untuk menyelesaikan persoalan penentuan siswa teladan disekolah. Kata kunci: Sekolah, Siswa Teladan, Sistem Pendukung Keputusan, Weighted product